Sexual abuse against boys in China: A life course perspective exploring the impact of abuse, and how social, cultural and policy matters influence survivors’ disclosure following sexual abuse - YIBO FAN (2024)
The discourse on child sexual abuse (CSA) usually centres on female survivors and male perpetrators; moreover, most existing research stems from socio-cultural contexts of Western nations like the United States and Europe. Thus, there is a paucity of CSA research within the Chinese socio-cultural and policy background. This leaves knowledge gaps regarding the vulnerability of Chinese male children, their barriers to disclosure, and the influence of Chinese socio-cultural norms and policies on CSA; together with the potential inadequacies of China’s social/legal policies on CSA this may result in insufficient support for male child survivors. The aim of this thesis is to explore potential risk factors for CSA during childhood, barriers to disclosure, and the perceived impacts of CSA on male children in China by interviewing male CSA survivors. This small-scale qualitative study utilises semi-structured interviews with 25 male survivors in China, most of whom were abused by other young people (including cousins, classmates, friends) and/or adult males (including authority figures, relatives, strangers); albeit four survivors reported abuse by females. The study reveals the risk factors and barriers to disclosure for CSA in Chinese male children include both familial and broader socio-cultural and policy-related factors within China. Although each survivor’s experience was unique, some common risk factors and barriers to disclosure were mentioned multiple times across different accounts. This commonality may stem from the similar ages among the survivors and their shared familial and socio-cultural backgrounds. Negative childhood experiences - such as parental separation brought about by rapid urbanisation in China; other forms of abuse; and external factors encompassing policies, laws, and cultural aspects, such as the one-child policy, lack of legal protection for male children, and the gender imbalance in sex education/sexual abuse prevention education - could all potentially be risk factors associated with child victimisation, and also impact the disclosure decisions made by survivors. Based on these accounts, this thesis proposes a model of vulnerability and a model of disclosure. Male survivors are less likely to report CSA compared to female survivors, resulting in a dearth of research on their abuse experiences and its “meaning” to them. This study was undertaken to give voice to a hidden population and to contribute towards more effective protection and intervention. The findings underscore the differences among survivor groups (that is, those abused by young people of a similar age; and/or female-perpetrated child sexual abuse, and/or male adult-perpetrated child sexual abuse) in terms of risk factors, barriers to disclosure, and the impacts of CSA. They also highlight the influence of China-specific socio-cultural, legal, and policy matters on male CSA survivors. To better support male CSA survivors, measures should begin with understanding the heterogeneity among male survivors and the influence of their personal circumstances and social environments on their vulnerability and willingness to disclose.